Pengaruh Project-Based Learning (PJBL) Berbasis Stem Terhadap Kemampuan Pemecahan Masalah Siswa SMA : Penelitian - Berta Masrifa Panggabean; Marni Anggi Sigalingging; Mariati Purnama Simanjuntak (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This research aims to determine the effect of the STEM-based project-based learning (PjBL) model on class XI students' problem-solving abilities in sound wave material. This type of research is quasi quasi-experiment with a two-group pretest-posttest design. This research sample consisted of two classes: class XI IPA 7 as the control class and XI IPA 9 as the experimental class. The instrument used is a problem-solving ability test in the form of a description that has been validated. Based on the research results, the average pretest and posttest scores in the control class were 43,58 and 67,45, and the experimental class average was 40 and 75. Based on the results of hypothesis testing using the difference test (t-test), sig (0.004) < 0.05 was obtained. Based on the N-gain test, it was obtained that the percentage increase in students' problem-solving abilities in the experimental class was 89% in the high category, and in the control class was 64% in the medium category. Based on statistical data, it can be concluded that there is an influence of implementing the STEM-based PjBL model on students' problem-solving abilities in sound wave material.